Draft Annual Plan 2003-2004 Volume II Government of Assam - Planning Commission (Planning Commission)
Draft Annual Plan 2003-2004 Proposed Outlay (GN - Statement) Draft Annual Plan 2003-04 Proposed Outlay Draft Tenth Plan 2002007 and Annual Plan 20020030 Proposed Outlay Physical Tara at and Achievement Summary Statement Draft Annual Plan (2003 - 2004) Proposals For Programmes/ Projects Statement Regarding Externally Aided Project
Government of Assam